Dracula [videorecording (DVD)] - Lugosi, Bela, 1882-1956; Manners, David, 1901-1998; Chandler, Helen, 1906-1965; Stoker, Bram, 1847-1912 ([Publisher not identified], 2014)
Although there have been numerous screen versions of Bram Stoker's classic tale, none is more enduring than the 1931 original.